Penerapan Metode WASPAS Pada Sistem Pendukung Keputusan Penentuan Tempat Wisata Kuliner - Elok Nur Hamdana; Dina Risky Alin Saputri; Deasy Sandhya Elya Ikawati (Universitas Budi Darma, 2023)
Culinary tourism is one of the tourist attractions when visiting an area with the aim of enjoying food with a certain taste. Culinary tourism in Batu City and Malang City offers a variety of culinary products, ranging from filling food to snacks such as typical and legendary dishes. So this creates its own problems for the community and tourists because they feel confused about making choices. Therefore, there is a need for a solution to this problem, namely by creating a decision support system that can help the community and tourists in determining culinary tourism spots appropriately according to their needs. This study uses the WASPAS (Weighted Aggregated Sum Product Assessment) method to calculate which culinary tourism spots are suitable based on the needs of the user or users. Based on this research, the system calculation using the WASPAS (Weighted Aggregated Sum Product Assessment) method on a culinary tourism decision support system can provide the right recommendation for users and users by using a Likert scale calculation obtained from the questionnaire results getting a final score of 88.95 %. From the test results using Spearman Correlation, correlation values are obtained of 0.6 and 0.8 which indicate that there is a relationship between the ratings generated by the system and the calculated rankings of people who like to eat.